Transdiagnostic treatment approaches for greater public health impact: Implementing principles of evidence‐based mental health interventions. Issue 4 (12th December 2018) - Martin, Prerna; Murray, Laura K; Darnell, Doyanne; Dorsey, Shannon
Abstract: There is a high burden of mental illness in low‐resource areas within the United States and in low‐ and middle‐income countries. Significant challenges in implementing focal treatments in these settings call for a shift toward alternative treatment approaches that have a greater public health impact. We use Glasgow et al's. ( American Journal of Public Health, 89, 1999, 1322) RE‐AIM framework, which prioritizes not only intervention effectiveness, but also the dimensions of reach, adoption, implementation, and maintenance. We suggest that transdiagnostic approaches, specifically those that are multiproblem, modular, flexible and of lower complexity, offer several advantages in low‐resource settings. We review their background, evidence, and specific characteristics that may advance RE‐AIM dimensions in low‐resource settings. We conclude with future directions to increase the public health impact of our mental health interventions.